Multivariate analysis to determine secondary characters in selecting adaptive hybrid corn lines under drought stress - NUR FADHLI; MUH. FARID; RAFIUDDIN; ROY EFFENDI; MUHAMMAD AZRAI; MUHAMMAD FUAD ANSHORI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fadhli N, Farid M, Rafiuddin, Efendi R, Azrai M, Anshori MF. 2020. Multivariate analysis to determine secondary characters in selecting adaptive hybrid corn lines under drought stress. Biodiversitas 21: 3617-3624. The development of adaptive hybrid corn varieties under drought stress needs an effective selection. Multivariate analysis has been reported can increase the effectiveness of selection in plants by attaching the secondary characters in the selection. Therefore, this concept also can be applied to develop adaptive corn varieties under drought stress. The objectives of this study are to determine the main secondary characters and select the best hybrid lines adaptive to drought stress. The experiment was arranged by a nested design, where replications nested under two environmental conditions, namely normal and drought stress. The main factor was genotypes consisted of 30 genotypes and was repeated three times. Moreover, the observations of this research consisted of 20 variables. The result of this research showed that the weight of harvested cob was an effective secondary character as a selection criterion along with productivity in selecting adaptive maize genotypes under drought stress. The number of green leaves was the character outside of the yield component could be as an alternative secondary character besides the weight of harvested cob. The selection results based on the weight of the harvested cob and productivity resulted in 12 hybrid corn lines considered adaptive to drought stress.